A Study on alpha-numeric brand naming - Kim, Yong-Ho (KDI School, 1998)
Brand extension strategy has been the core of strategic growth for a variety of companies in the last decade. However, the extension can damage the original brand equity by weakening the existing associations or adding new undesired ones. Alpha-numeric brand naming can be proposed as a new alternative. This study has examined two successful cases of alpha-numeric brand naming strategy launched in the Korean car industry. First, it was proved that alpha- numeric brand can be effectively used when the high- tech products are launched in the market. Second, the launching of alpha-numeric brand offered opportunities for brand extension. And effective alpha- numeric brand naming placed its current modifier- type of numeric to the identical status with the alphabet.
Thesis(Master) --KDI School:Master of Strategy & International Management,1998